THU0421 Rheumatoid Versus Psoriatic Arthritis: Similar or Different Bone Loss?. (23rd January 2014) - Paolino, S.; Botticella, G.; Casabella, A.; Meroni, M.; Molfetta, L.; Cutolo, M.; Seriolo, B.
Abstract : Background: Rheumatoid (RA) and psoriatic (PsA) arthritis are chronic diseases characterized by inflammation, often common therapies and prolonged joint immobilization are possible risk factors of bone loss and fragility fractures. 1 Vitamin D is a key regulator of calcium homeostasis and skeletal health, but also seem to play an important role as risk factor for RA and PsA Objectives: to determine bone mineral density (BMD) and 25-dihydroxyvitaminD3 [25(OH)D3 ] serum concentrationin RA and PsA patients Methods: The study included 61 postmenopausal patients (mean age 65±8 years) affected by RA, 45 PSA symmetrical type (mean age 63±4 years) and 31 age-matched healthy controls. BMD at the lumbar spine (L1-L4) and at the proximal femur was analyzed using dual-energy X-ray absorptiometry (DXA) scan (Lunar Prodigy, GE, USA). The results of BMD were expressed in g/cm 2 and the diagnosis of osteoporosis was defined according to WHO guidelines as T-score less -2.5 whereas osteopenia as T-score between -1.0 and -2.5 at any site. Laboratory assessment included quantitative determination of 25(OH)D3 concentration performed by DiaSorin radioimmunoassay kit and the cut-off defined according to international guidelines 2 . Results: Among the 45 patients with PsA, 5 (11%) presented osteoporosis and 15 (33%) osteopenia. Fifteen RA patients(25%) showed an osteoporotic condition and 14 (23%) an osteopenic status. BMD, T and Z scores at lumbar spine and at all site of femur were found significantly lower in RA and PsA patients than in control group. 25(OH)D3 concentration were (RA: 13.9±8.0 ng/mL vs PsA: 15.9±7.4 ng/mL vs 44.8±4.7 ng/mL p<0.001). BMD was significantly lower in the RA than in PsA patients (femoral neck: BMD 0.781±0.11 g/cm 2 vs 0.823±0.10 g/cm 2 p=0.02; ward: BMD 0.582±0.13 g/cm 2 vs 0.663±0.11 g/cm 2 p=0.02; trocanther: BMD 0.668±0.13 g/cm 2 vs 0.714±0.08 g/cm 2 p=0.01). Similarly, the T-score value in all site determined were lower in RA versus PsA patients (femoral neck: -1.6 ±1.0 vs-1.2±0.88 p=0.01; ward:-2.4 ±1.0 vs -1.9±0.9 p=0.02; trocanther: - 1.1 ±1.2 vs -0.8± 0.8 p=0.03; total hip: T-score -1.4±1.2 vs-0.88±1.0 p=0.03). A significant positive correlation was found between T and Z scores at lumbar spine in RA and 25(OH)D3 concentration (r=0.28 p=0.02 and r=0.27 p=0.03); as well in PsA group 25(OH)D3 was related to BMD, T-score and Z-score at all site of evaluation of femur. (Femoral neck BMD: r=0.69 p<0.001, T-score: r=0.68 p<0.001, Z-score: r=0.63 p<0.001; Ward BMD r=0.54 p=0.001, T-score:r=0.54 p=0.001, Z-score: r=0.54 p<0.001; Trocanther: BMD: r=0.42 p=0.03; T-score: r=0.59 p<0.001, Z-score:r=0.42 p=0.003;Total hip: BMD:r=0.67 p<0.001, T-score: r=0.52 p=0.002) Conclusions: This study reports that bone loss occurs both in RA and in PsA patients, but overall BMD decrease was less evident in PsA patients. In both diseases insufficient/deficient levels of vitamin D are correlated with BMD decrease. The most intensive chronic inflammation in RA patients might partially explain their most evident systemic bone loss versus PsA patients. References: Simeon Grazio et al. Osteoporosis in psoriatic arthritis:is there any? Wien Klin Wochenschr 2001;123:743-750 Holick MF. Vitamin D deficiency. N.Engl J Med 2007;357:266-281 Disclosure of Interest: None Declared